Nucleophilic nitration of arynes by sodium nitrite and its multicomponent reaction leading to double-functionalized arenes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Organic Letters, 2016)
An unusual nucleophilic nitration of arynes by NaNO2 in the presence of water has been developed, and the concept was further demonstrated to accomplish a double functionalization of arynes using a multicomponent reaction protocol to synthesize pharmaceutically important (2-nitrophenyl)methanol derivatives. Such substitution ortho to -NO2 is difficult by other means. The reaction conditions are mild and avoid the use of strong acids, expensive transition metal catalysts, and additives.